Complications and management strategies of totally implantable venous access port insertion through percutaneous subclavian vein - Velioğlu, Yusuf (Turk Gogus Kalp Damar Cerrahisi Derg, 2019)
BACKGROUND: The aim of this study was to present clinical characteristics, peri-procedural outcomes, early and late complications, and management strategies in patients undergoing totally implantable venous access port insertion through percutaneous subclavian vein. METHODS: A total of 2,084 port devices were inserted to 2,000 cancer patients (1,066 males, 934 females; mean age 58.4±12.7 years; range, 18 to 88 years) through subclavian vein using percutaneous landmark method between March 2012 and June 2018. Medical data including demographic features, primary diagnosis, technical success, procedural time, duration of device use, reasons for the device removal, and early and late complications were retrospectively analyzed. RESULTS: The most common type of cancer was colon cancer in males and breast cancer in females. Technical success rate of the procedure was 98.5%. Right subclavian vein was accessed in the majority of patients (92.4%). Early complications including inadvertent arterial puncture, catheter malposition, superficial hematoma, and pneumothorax occurred in 143 patients (6.9%), while late complications including infection, catheter occlusion, venous thrombosis, wound problems, catheter migration and embolization and pinch-off syndrome was developed in 118 patients (5.7%). Inadvertent arterial puncture in 63 patients (3%) was the most common early complication, while infection in 44 patients (2.1%) was the most common late complication. A total of 192 devices were removed due to the completion of chemotherapy or development of complications. CONCLUSION: Our study confirmed the safety and tolerability of totally implantable venous access port insertion through percutaneous subclavian vein with high technical success and low complication rates.